1977
DOI: 10.3109/15563657708989823
|View full text |Cite
|
Sign up to set email alerts
|

Association between Renal Function Tests and Pentachlorophenol Exposure

Abstract: Data are presented and renal function tests and Pcp measurements on consecutive blood and urine samples collected from 18 workers at a wood treatment plant before, during, and after a 20-day vacation. Pcp concentrations in blood averaging 5.1 ppm before vacation fell to 2.2 ppm during vacation but with a temporary rise early in this nonexposure period, suggesting a body tissues store of Pcp which was mobilized in response to a negative Pcp balance. Urine Pcp concentrations showed similar but less marked variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 10 publications
1
19
0
1
Order By: Relevance
“…A slight negative hydrostatic pressure was applied to the lower chamber to help secure the cornea to the copper grid. Control (regular) solutions contained (in mM) (stroma): Na + , 102; K + , 4.0; Ca 2+ , 1; Mg 2+ , 0.8; Cl − , 106.2; SO 4 2− , 0.8; phosphate, 1; and glucose, 10; (tear): Na + , 100; K + , 4; Ca 2+ , 1; Cl − , 97; HCO 3 − , 5; phosphate, 1; and glucose, 10. K + was substituted for Na + in high K + solutions.…”
Section: Methodsmentioning
confidence: 99%
“…A slight negative hydrostatic pressure was applied to the lower chamber to help secure the cornea to the copper grid. Control (regular) solutions contained (in mM) (stroma): Na + , 102; K + , 4.0; Ca 2+ , 1; Mg 2+ , 0.8; Cl − , 106.2; SO 4 2− , 0.8; phosphate, 1; and glucose, 10; (tear): Na + , 100; K + , 4; Ca 2+ , 1; Cl − , 97; HCO 3 − , 5; phosphate, 1; and glucose, 10. K + was substituted for Na + in high K + solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Short-term respiratory exposure may result in transient mild liver dysfunction (increased bilirubin, serum glutamatepyruvate and oxaloacetic-pyruvate transaminases, and -glutamyl transferase) with abnormal porphyrin metabolism (increased uroporphyrin and -aminolevulinic acid) (Fielder et al, 1982;Jirasek et al, 1974;Kozak et al, 1979). Reversible renal function changes (decreased creatinine clearance and phosphaturia) have been described (Begley et al, 1977). There are no clinical indications of peripheral neuropathy, although exposed workers have been shown to have decreased sensory nerve conduction rates (Triebig et al, 1981).…”
Section: Metabolism and Toxicokineticsmentioning
confidence: 99%
“…The chronic effects of exposure to PCP have been studied in PCP production workers (4-10), PCP formulators (11), wood treatment workers (12,13), sprayers (11), and sawmill workers (14)(15)(16). Several studies have demonstrated that exposure to commercial PCP can produce chloracne (4,8-10,17,18).…”
mentioning
confidence: 98%